Did erly pleistocene hominins control hammer strike angles when making stone tools? - Li, Li (2023)
In the study of Early Pleistocene stone artifacts, researchers have made considerable progress in reconstructing the technical decisions of hominins by examining various aspects of lithic technology, such as reduction sequences, hammer selection, platform preparation, core management, and raw material selection. By comparison, our understanding of the ways in which Early Pleistocene hominins controlled the delivery and application of percussive force during flaking remains limited. In this study, we focus on a key aspect of force delivery in stone knapping, namely the hammerstone striking angle (or the angle of blow), which has been shown to play a significant role in determining the knapping outcome. Using a dataset consists of 12 Early Pleistocene flake assemblages dated from 1.95 Ma to 1.4 Ma, we examined temporal patterns of the hammer striking angle by quantifying the bulb angle, a property of the flake's Hertzian cone that reflects the hammer striking angle used in flake production. We further included a Middle Paleolithic flake assemblage as a point of comparison from a later time period. In the Early Pleistocene dataset, we observed an increased association between the bulb angle and other flake variables related to flake size over time, a pattern similarly found in the Middle Paleolithic assemblage. These findings suggest that, towards the OldowaneAcheulean transition, hominins began to systematically adjust the hammer striking angle in accordance with platform variables to detach flakes of different sizes more effectively, implying the development of a more comprehensive understanding of the role of the angle of blow in flake formation by similar to 1.5 Ma.